Ischemic stroke due to minor head trauma in a child: a case report - Eraybar, Suna; Katı, Yalçın; Atmaca, Serhat; Torun, Gökhan; Nennicioğlu, Yasemin (The European Research Journal, 2019)
Head trauma usually causes hemorrhage, but in children ischemia of basal ganglia may develop. Traumatic stroke occasionally develops after dissection of brain vessels, leading to disseminated cerebral embolism. Stretching forces in cerebral intraparenchymal arteries can cause vascular damage followed by an occluding thrombus. An 18-month-old girl presented to our emergency department with the complaint of head trauma after falling down while playing. Her parents recognized the weakness of her left site extremity after 6 hours after the event. After initial physical examination and further imaging studies brain magnetic resonance imaging (MRI) showed an infarct affecting the caudate nucleus in the right cerebral hemisphere. In childhood, ischemic stroke due to mild head trauma is an exceedingly rare event and may be overlooked in emergency medicine practice. We aimed to emphasize that mild head trauma may cause critical situations such as acute infarct in children.